Uma jornada gamificada para o desenvolvimento das competências gerais da educação básica em aulas de matemática no 9º ano do ensino fundamental - Zanette, Gustavo Henrique (2023)
This research is characterized as action research that deals with the use of gamification in a 9th grade class of the public education network in the state of Paraná during the teaching and learning process in mathematics. As part of this study, the guiding question was adopted: What do 9th grade elementary school students say about the use of structural gamification applications in the subject of mathematics in relation to the general competencies included in the National Common Curricular Base? As specific objectives, we wanted to find out which general skills are influenced using structural gamification and analyze whether this gamification promotes the development of these skills through students' understanding. First, a systematic literature review was conducted on how gamification has been understood and achieved in mathematics education and in postgraduate mathematics education research. Then, the development and application of a didactic proposal in a gamified environment was approached in a structural way, with content related to the second and third quarters of the 9th year of elementary school graduation classes, mediated by the Octalysis gamification model, to observe the nuances that arise from gamification beyond motivation and engagement. Finally, using a semi-structured questionnaire with descriptive questions, an analysis of the implemented gamification experience was conducted, guided by the content analysis method. As a result, the improvement of eight general skills as well as changes in students' attitudes during the lesson and in the work of the teacher/researcher were measured